Responding to the needs of the community: Evolving nature of the Canadian Perspectives on Academic Integrity - Usick, Brandy; Stoesz, Brenda M (Canadian Perspectives on Academic Integrity, 2021)
In this editorial, we reflect on the origins of the Canadian Perspectives on Academic Integrity and provide an overview of the evolution of this journal. Despite its continued development, an important goal has remained: Creating “space for practitioners to connect and feel connected to one another on a professional level” (Eaton, 2018, p. 1).